Exploring the Gap Between Grammar Knowledge and Written Production in Chinese Senior High EFL Classrooms: A Proceduralisation Perspective - Qi, Weiran (Transactions on Social Science, Education and Humanities Research, 2026)
This paper investigates the continuous discrepancy between knowledge of declarative grammar and written production in Chinese senior high school English as a Foreign Language (EFL) classrooms. According to the theory of cognitive skill acquisition and the shift from declarative to procedural knowledge, this paper investigates why learners may have difficulty applying explicitly learned grammatical rules in spontaneous written production. Form-oriented teaching can help students learn the grammar explicitly, but many students are still unable to apply this knowledge correctly and flexibly in extended writing. Based on the above analysis, some traditional teaching methods focus on isolated grammar drills and offer fewer opportunities for extended, meaningful practice that supports proceduralisation. In addition, this paper will also examine how prompted output and suitable writing tasks can help learners notice deficiencies in their interlanguage and gradually reorganise their grammatical knowledge. Grammar learning can be viewed as a process of proceduralisation in this paper, and explicit rules gradually turn into more automatic language use; therefore, pedagogical suggestions for classroom teaching are proposed. Integrated task-based writing activities can help learners gradually internalise the explicit grammatical rules in their writing through practice.